Victorian biography reconsidered : a study of nineteenth-century 'hidden' lives - Atkinson, Juliette (Oxford : Oxford University Press, 2010)
Through an examination of numerous biographies, from the lives of working-class scientists to minor women writers, 'Victorian Biography Reconsidered' examines how and why 19th-century biographers challenged the contemporary obsession with 'great men' and brought to public attention the lives of neglected or unknown men and women.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed Sept. 7, 2010).
Keywords: Biography -- 19th century